2011
DOI: 10.1063/1.3670877
|View full text |Cite
|
Sign up to set email alerts
|

Conformational fluctuations of a protein–DNA complex and the structure and ordering of water around it

Abstract: Protein-DNA binding is an important process responsible for the regulation of genetic activities in living organisms. The most crucial issue in this problem is how the protein recognizes the DNA and identifies its target base sequences. Water molecules present around the protein and DNA are also expected to play an important role in mediating the recognition process and controlling the structure of the complex. We have performed atomistic molecular dynamics simulations of an aqueous solution of the protein-DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…We note that the local tetrahedral metric is a very convenient metric for measuring the local structure of water at biomolecular as well as inorganic interfaces. [72][73][74][75][76][77][78][79][80][81] The tagged molecule potential energy (TPE or u tag ), defined as the interaction energy of an individual water molecule with all other molecules in the system, is a convenient measure of local energy. [82][83][84][85][86] The TPE can also be considered as the binding energy of an individual water molecule in the system.…”
Section: Characterizing Order and Energetics In The Hydration Layermentioning
confidence: 99%
“…We note that the local tetrahedral metric is a very convenient metric for measuring the local structure of water at biomolecular as well as inorganic interfaces. [72][73][74][75][76][77][78][79][80][81] The tagged molecule potential energy (TPE or u tag ), defined as the interaction energy of an individual water molecule with all other molecules in the system, is a convenient measure of local energy. [82][83][84][85][86] The TPE can also be considered as the binding energy of an individual water molecule in the system.…”
Section: Characterizing Order and Energetics In The Hydration Layermentioning
confidence: 99%
“…Map describing the interactions between TRF1 and telomeric DNA as determined by solution NMR (Protein Data Bank entry 1IV6 16 ). Direct readout (red line), indirect readout (black dotted line), and hydrophobic patches (black broken line) are delineated.…”
Section: Figmentioning
confidence: 99%
“…Molecular dynamics (MD) simulation provides an important alternative method that has been used over the years to explore the properties of hydrated protein–DNA complexes. In particular, water-mediated interactions between the protein and the DNA molecules in complexed states have been studied. , Recently, Poon and co-workers discussed the role of water in protein–DNA recognition. They demonstrated that configurationally similar water-mediated contacts play a distinct role during the recognition process of the DNA by the transcription factors belonging to the ETS-Family.…”
Section: Introductionmentioning
confidence: 99%